The application of Quality Function Deployment (QFD) and Rapid Prototyping (RP) technology in improving the design of anti sleep driving alarm - Wan Yusoff, Wan Ahmad Yusmawiza; Adesta, Erry Yulian Triblas; Dahnel, Aishah Najiah; Abd Halim, Nor Farah Huda (IEOM Research Solutions Pty Ltd, 2011)
The purpose of this research is to apply Rapid Prototyping (RP) technique using Fused Deposition Modelling (FDM) in improving the design of anti sleep driving alarm. Quality Function Deployment (QFD) is introduced as a quality tool to analyze and evaluate the criteria and characteristics of the part to be improved. The analysis from QFD and House of Quality is translated into several possible concept designs by utilizing computer aided drafting. The prototypes of the concept designs fabricated using FDM machine are evaluated using concept scoring to determine the most promising concept designs. This research is limited to part build by fused deposition modelling RP process and also to the availability of material, however, the concepts experimented may be applied for other RP processes.